Pendampingan KIR Menuju Kompetisi Myres MAN Kota Pasuruan - Mizam Ari Kurniyanti; Miftakhul Ulfa; Ahmad Guntur Alfianto; Ari Dwi Sulaksono (I-Com: Indonesian Community Journal, 2024)
Madrasah Young Researchers Supercamp (Myres) is a national competition held by the ministry of religion that can be followed by all schools under territory ministry of religion . MAN Kota Pasuruan is one of the schools that participated in the competition, and in order for students' scientific work proposals to get Myres grants, intensive assistance is needed in its preparation. The purpose of this activity is to assist students in preparing scientific proposals through training and mentoring methods for writing adolescent scientific proposal so that they can join in the Myres competition. The results of this activity are an increase in student knowledge related to the preparation of adolescent scientific papers, the preparation of 17 scientific proposals submitted in the Myres competition and 1 team that passed the national level selection.